STUDI TENTANG KERJA SAMA INTERNATIONAL CRIMINAL POLICE ORGANIZATION (ICPO-INTERPOL) DENGAN POLRI DALAM MENANGKAP PELAKU KEJAHATAN YANG MELARIKAN DIRI KELUAR NEGERI - Zuan Driza; Arif Arif; Sutiarnoto Sutiarnoto (Journal of USU International Law, 2013)
ABSTRACT This study entitled "Study on cooperation Internastional Criminal Police Organization (ICPO-INTERPOL) with the police in capturing criminals who escaped out of the country". The problem to be answered in this study is how the position of ICPO-INTERPOL in International Law and how its authority to cooperate with the POLRI, and then to understand why the return of escaped criminals out of the country often run into obstacles. The issue is expected to be answered by using the method of normative research which refers to the legal norms contained in legislation and court decisions and legal norms in society. The main data used are secondary data collected through the study of literature methods or documents. While the primary data collected from the Convention and legislation relating to the object of research. The data that has been obtained is qualitative data will be analyzed and the analysis of primary data and secondary data from a qualitative point of view of jurisprudence. Through the techniques of data collection and data analysis of this study is expected to achieve the desired goal, which is to determine the position of ICPO-INTERPOL in international law, ICPO-INTERPOL knowing authority in cooperation with the police and understand why the return of criminals fleeing abroad often experience barriers.